Optimization of Process Parameters and Post-Processing of SLA 3D Printing on the Hardness of Photopolymer Resin Using the Taguchi Method - Candra Hadi Prayoga; Abdul Hamid; Prabuditya Bhisma Wisnu Wardhana; Mega Lazuardi Umar; M. Abdul Wahid (Universitas Islam Malang, 2026)
The limited availability of plastic components for classic automotive vehicles has encouraged the utilization of stereolithography (SLA) 3D printing technology as an alternative manufacturing method. However, studies regarding the optimization of SLA printing and post-processing parameters on the hardness characteristics of photopolymer resin are still limited. This study aimed to optimize SLA process and post-process parameters to improve resin hardness. The investigated parameters were layer thickness, exposure time, washing time, and curing time. The experimental design employed the Taguchi method with an L9 (3⁴) orthogonal array. Specimens were fabricated using an Anycubic Photon Mono 2 printer ABS-Like Resin Pro 2 material, followed by washing and curing processes according to experimental parameters. Hardness testing was conducted using the Shore D method based on ASTM D2240 standards. The experimental data were analyzed using signal-to-noise (S/N) ratio analysis, analysis of variance (ANOVA), and percentage contribution analysis with Minitab software. The results indicated that layer thickness exhibited the highest contribution ratio (47.24%), followed by exposure time (34.62%) and washing time (14.21%). However, ANOVA results indicated none of the investigated factors were statistically significant at the 95% confidence level (p > 0.05). The optimal parameter combination consisted of 0.20 mm layer thickness, 9 s exposure time, 5 min washing time, and 20 min curing time. Confirmation experiments produced a hardness value of 87.8 Shore D, which was close to the predicted value of 88.0333 Shore D. These findings demonstrate that Taguchi method is effective for determining optimal SLA printing parameters to enhance photopolymer resin hardness.